PENGARUH DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS BAWANG MERAH (Allium ascalonicum L.) DI DESA PENGARINGAN KABUPATEN KEBUMEN - Rini Pujiatun; Umi Barokah (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2026)
Shallots are a strategic commodity whose production in Pengaringan Village, Kebumen, is still constrained by the optimization of varieties and fertilizer dosages. This study aims to analyze the growth response of two shallot varieties to various dosages of NPK 16-16-16 fertilizer. The research method employed a Factorial Randomized Complete Block Design (RCBD) with two factors: variety (Bima Brebes and Tajuk) and NPK dosage (0; 1.2; 2.4; and 3.6 g/polybag).The variables observed included plant height, number of leaves, number of tillers, number of bulbs, bulb diameter, fresh bulb weight, and dry bulb weight. Data were analyzed using ANOVA followed by DMRT (Duncan’s Multiple Range Test) at a 5% significance level.The results showed that the variety factor significantly affected plant height, number of tillers, and bulb diameter. Meanwhile, the fertilizer factor and the interaction between variety and NPK dosage had no significant effect on any of the variables. The Bima Brebes variety was found to be the superior variety for plant height, whereas the Tajuk variety was the superior variety for the number of tillers and bulb diameter.